A simple melting-diffusing-reacting strategy to fabricate S/NiS2–C for lithium–sulfur batteries. Issue 40 (3rd October 2016) - Lu, Yue; Li, Xiaona; Liang, Jianwen; Hu, Lei; Zhu, Yongchun; Qian, Yitai
Abstract : A melting-diffusing-reacting strategy has been developed to fabricate S/NiS2 –C composites, which demonstrated superior electrochemical properties and are promising cathode materials for lithium–sulfur batteries. Abstract : S/NiS2 –C composites were fabricated using a sample melting-diffusing-reacting strategy. When the elemental sulfur content in the composite is 54.9 wt%, it shows good cyclic performance and delivers a specific capacity of 730 mA h g −1 after 200 cycles at 0.5 C and 544 mA h g −1 after 500 cycles at 2 C. The elemental sulfur content can be adjusted, and when the elemental sulfur content is increased to 64.8 wt% and 76.0 wt%, the cathodes can maintain a stable cyclic capacity of 386 and 312 mA h g −1 after being discharged/charged at 2 C for 500 cycles respectively. The carbon structure and the uniformly distributed nickel disulfide in the S/NiS2 –C composites efficiently stabilizes the polysulfides and also facilitates the conversion of electrochemical reactions.